How to derive the formulas for hyperbolic sine?

The formula for hyperbolic sine is derived from the exponential function.

To derive the formula for hyperbolic sine, we start with the exponential function:

e^x = 1 + x + (x^2)/2! + (x^3)/3! + ...

We can rewrite this as:

e^x = 1/2 (e^x + e^-x) + 1/2 (e^x - e^-x)

Now, let y = e^x - e^-x. Solving for e^x and e^-x, we get:

e^x = (y + sqrt(y^2 + 4))/2
e^-x = (sqrt(y^2 + 4) - y)/2

Substituting these expressions into the equation for y, we get:

y = e^x - e^-x = (y + sqrt(y^2 + 4))/2 - (sqrt(y^2 + 4) - y)/2

Simplifying, we get:

y^2 = (e^x - e^-x)^2 = (y + sqrt(y^2 + 4))(sqrt(y^2 + 4) - y)

Expanding and simplifying, we get:

y^2 = 4 sinh^2(x)

Therefore, the formula for hyperbolic sine is:

sinh(x) = (e^x - e^-x)/2

Study and Practice for Free

Trusted by 100,000+ Students Worldwide

Achieve Top Grades in your Exams with our Free Resources.

Practice Questions, Study Notes, and Past Exam Papers for all Subjects!

Need help from an expert?

4.93/5 based on525 reviews

The world’s top online tutoring provider trusted by students, parents, and schools globally.

Related Maths a-level Answers

    Read All Answers
    Loading...